Pengaruh Burnout Terhadap Kinerja dengan Kecerdasan Emosional dan Self-Efficacy Sebagai Pemediasi Pada Guru SLB di Kota Ternate - Mariyani Hi. Tamrin; Said Hasan; Abdul Rahman Jannang (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the effect of burnout on increasing intelligence and self-efficacy as a mediator. In this study, what functions as the variable used is burnout, and emotional intelligence and self-efficacy variables as mediating variables, while job performance variables as variables are brought. The population in this study published all Special School Teachers (SLB) in Ternate City and obtained a total sample of 62 respondents. The analytical method used in this study is path analysis with the help of the SPSS application. From the results of hypothesis testing conducted, it was found that burnout has a negative and significant effect on performance, burnout has a negative and significant effect on emotional intelligence, burnout has a negative and significant effect on self-efficacy, positive emotional intelligence and a significant effect on performance, self-efficacy, positive and significant to performance, and emotional intelligence and self-efficacy variables are able to mediate the effect of burnout on performance